2015
DOI: 10.1038/ncomms8840
|View full text |Cite
|
Sign up to set email alerts
|

Snf1/AMP-activated protein kinase activates Arf3p to promote invasive yeast growth via a non-canonical GEF domain

Abstract: Active GTP-bound Arf GTPases promote eukaryotic cell membrane trafficking and cytoskeletal remodelling. Arf activation is accelerated by guanine nucleotide-exchange factors (GEFs) using the critical catalytic glutamate in all known Sec7 domain sequences. Yeast Arf3p, a homologue of mammalian Arf6, is required for yeast invasive responses to glucose depletion. Here we identify Snf1p as a GEF that activates Arf3p when energy is limited. SNF1 is the yeast homologue of AMP-activated protein kinase (AMPK), which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…Four isolates possessed SNP R188Q in Snf1 kinase; this protein is known to be involved in nutrient limitation and salt stress responses in Saccharomyces cerevisiae ( Hsu et al, 2015 , Sanz, 2003 ). It is possible that R188Q alters Snf1 functionality, potentially enhancing the ability of the isolates to cope with these stresses, which could enable persistence of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Four isolates possessed SNP R188Q in Snf1 kinase; this protein is known to be involved in nutrient limitation and salt stress responses in Saccharomyces cerevisiae ( Hsu et al, 2015 , Sanz, 2003 ). It is possible that R188Q alters Snf1 functionality, potentially enhancing the ability of the isolates to cope with these stresses, which could enable persistence of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Snf1 also regulates Arf3 134 , one of the ADP-ribosylation factors (Arfs), involved in vesicle transport and actin reorganization. Yeast Arf3 is required for invasive growth and its activity is stimulated upon glucose-depletion in a Snf1-dependent manner.…”
Section: Non Conventional Roles Of Snf1mentioning
confidence: 99%
“…However, the peculiarity of the activation of Arf3 is that it does not depend on Snf1 kinase activity, but rather on its absolutely new role as a GEF (Guanine Nucleotide Exchange Factor). In fact, it was shown that the C-terminal hydrophobic α-helix core of Snf1 is a non-canonical GEF for Arf3 activation 134 .…”
Section: Non Conventional Roles Of Snf1mentioning
confidence: 99%
“…In recent years, AMPK has received increasing attention, for its role in overall growth and reproduction in many organisms, and for its potential as a therapeutic target ( 28 33 ). In both yeast and Drosophila , AMPK is essential for regulating nutrient uptake and proper organismal growth, as the absence of AMPK abrogates nutrient uptake and storage and results in abnormal or delayed growth, and is sometimes lethal ( 34 36 ). In Caenorhabditis elegans , AMPK plays a fundamental role in formation of dauer larvae, a developmental stage triggered by limited environmental nutrient availability that exhibits decreased metabolic activity and rationing of energy stores—a state that is similar to the phenotype of schistosomes isolated from immunodeficient mice ( 37 39 ).…”
Section: Introductionmentioning
confidence: 99%